Entre le père biologique et le père spirituel : le choix de la rupture chez les personnages de Boubacar Boris Diop - Seye, Serigne (Romanica Silesiana)
This article is aimed at analyzing the break between fathers and their children in the texts of Boubacar Boris Diop, in which another figure often replaces that of the biological parent. Participating in the identity construction of his foster son, the spiritual father grants him memory which is contradictory to the official history. This clash, omnipresent in Boubacar Boris Diop’s novels, testifies of a change of paradigm revealing a deep crisis of the father figure in African postcolonial societies. We are indeed very far from the mythicized image of the pater nobilis which used to be omnipresent in African literature.